Structural evolving appetitive reward-based pseudo-outer-product fuzzy neural network SE-ARPOP-CRI(S) - Do, The Anh (2012)
Inspired by ARPOP-CRI(S) (Appetitive Reward-based Pseudo-Outer-Product Fuzzy Neural Network), a sequential learning model that incorporates the concepts of pre-synaptic and synaptic inspirations in Aplysia feeding behaviour, the student decided to build a new computational model that supports both structure learning as well as parameter learning in an online learning process. The model are constructed with preservation of features that support ARPOP-CRI(S) to deal with di culties in processing dynamic data stream as well as novel points that help the model with a better generality and performance.